Lack of association between ABO histo-blood groups, secretor and non-secretor phenotypes, and anti-Toxoplasma gondii antibodies among pregnant women from the northwestern region of São Paulo State, Brazil - Brandao de Mattos, Cinara C. [UNESP]; Cintra, Juliana R.; Ferreira, Ana I.C.; Spegiorin, Ligia C.J.F.; Galisteu, Katia J.; Machado, Ricardo L.D. [UNESP]; de Mattos, Luiz Carlos [UNESP] (My University, 2008)
Introduction: Toxoplasma gondii infects humans in several manners including by the gastrointestinal tract where a-2-L-fucosyltransferase (FUTII) coded by the FUT2 gene (19q13.3) controls the expression of the ABH glycoconjugate profile. The presence of functional FUTII defines the secretor phenotype which is associated with ABO erythrocytic phenotypes. Due to the epidemiological and clinical importance of T. gondii infection, the aim of this work was to test the hypothesis that the ABH glycoconjugate profile expressed in the gastrointestinal tract is associated with the presence of antibodies against this parasite. Material and methods: A total of 367 pregnant women from the High-Risk Pregnancy Clinic of the University Hospital de Base in São José do Rio Preto were enrolled in this study. Two blood samples were drawn with only one being mixed with anticoagulant. ABO erythrocytic phenotyping and detection of anti-T. gondii antibodies were achieved by the haemagglutination test. Identification of the secretor status used the PCR-RFLP method. Results: Differences in the ABO erythrocytic phenotypes (P=0.20) and secretor and nonsecretor phenotypes (P=0.41), either in isolation or in association, were not statistically significant with respect to the presence or absence of anti-T. gondii antibodies. Conclusions: These results suggest that the ABH glycoconjugate profile expressed in the gastrointestinal tract under regulation of the FUT2 gene is not associated with anti-T. gondii antibodies. Copyright © 2008 Termedia & Banach.
Keywords: ABO histo-blood groups; FUT2 G428A; FUT2 gene; Secretor status; Toxoplasma gondii